2021
DOI: 10.1002/pts.2610
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of organic acids turns classically brittle zein films into flexible antimicrobial packaging materials

Abstract: This study aimed to turn classically brittle zein films into flexible antimicrobial ones by the use of lactic (LA), malic (MA) and tartaric acids (TA). The most effective plasticizer was LA (400% elongation at break [EB] at 4%), while MA (189% EB at 4.5%) and TA (68% EB at 5%) showed moderate and limited plasticizing effects, respectively.The LA-and MA-loaded films maintained their flexibility during 30-day storage at 4 C or 25 C. Fourier transform infrared (FTIR) analysis suggested that the plasticization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The tensile strength of packaging materials are not greatly affected when only small quantities of antimicrobial agents are incorporated or when the molecular weight of the antimicrobial agent is less than that of polymer materials (Bastarrachea et al, 2011). For instance, the addition of 2.00-2.50% (w/w) of malic acid did not significantly affect the tensile strength of zein films (Sözbilen, Çavdaroğlu, & Yemenicioğlu, 2022). Similar results were obtained when low concentrations of cinnamon, thyme or lemon EO was incorporated into biodegradable films (Peng & Li, 2014;Syafiq et al, 2021).…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 98%
See 4 more Smart Citations
“…The tensile strength of packaging materials are not greatly affected when only small quantities of antimicrobial agents are incorporated or when the molecular weight of the antimicrobial agent is less than that of polymer materials (Bastarrachea et al, 2011). For instance, the addition of 2.00-2.50% (w/w) of malic acid did not significantly affect the tensile strength of zein films (Sözbilen, Çavdaroğlu, & Yemenicioğlu, 2022). Similar results were obtained when low concentrations of cinnamon, thyme or lemon EO was incorporated into biodegradable films (Peng & Li, 2014;Syafiq et al, 2021).…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 98%
“…Zein films containing organic acids, such as lactic acid, malic acid and tartaric acid, exhibited greater elongation at break than control films due to their plasticizing effect (Sözbilen et al, 2022). Khaneghah et al (2018) and Varghese et al (2020) suggested that the incorporation of most EO and plant extracts to polymer materials typically reduces the tensile strength and improves the elongation at break of food packaging films.…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations